Trans fatty acids in selected bakery products and its potential dietary exposure - S., Siti Nurshahbani; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
High intake of trans fatty acids (TFA) may cause adverse changes in blood lipids as shown in many epidemiological studies. The major sources of TFA in human diet come from bakery products such as cookies, cakes, muffins, breads and pastries. In this study, total fat of baked products was determined using Soxhlet method while TFA content was determined on gas chromatograph using a highly polar capillary column and flame ionization detector. Exposure to TFA from the baked product was estimated based on Food Consumption Statistics of Malaysia 2003. High level of TFA was observed in muffins (3.21-7.34 g per 100 g food) followed by pastries (2.90-6.03 g per 100 g food) and cakes (2.26-8.36 g per 100 g food) regardless of products having brand name or not. Among the TFA isomers, trans 18:1 6t was the most abundant followed by trans 18:1 9t, trans 16:1 9t, trans 18:2 and small quantities of trans 18:1 11t. Exposure to TFA based on the Malaysian Food Consumption Statistics 2003 of the baked products was ranging from 0.14-0.18 g/day. Even with the low estimated exposure, actual intake of baked products must be monitored closely as other high fat food as these products is one of main contributor to TFA in the diet following their high frequency of daily intake.